EVALUATION OF VISUAL OUTCOME AND CLINICAL RESPONSE OF INTRAVITREAL ANTI VEGF AGENTS IN VARIOUS INDICATIONS - KHANDELWAL, GARVITA; KUMAR, KAVITA; DUBEY, ADITI; SOM, VIVEK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to evaluate efficacy of ranibizumab and aflibercept in Choroidal neovascular membrane (CNVM) and chronic macular edema secondary to diabetes mellitus and retinal vein occlusion in the Central India population. Methods: The present study was a prospective and observational study conducted among patients attending the outpatient department, and retina clinic were grouped as per various indications of anti-vascular endothelial growth factor (anti-VEGF) treatment. Patients were then followed up on day 7, 1-month interval during which visual acuity assessment, fundus examination, and optic coherence tomography was done to measure central retinal thickness which was compared with baseline data. Results: Two different anti-VEGF agents were used among study participants. Out of 43 study participants, ranibizumab was given in 32 (74.4%) of which seven patients had age-related macular degeneration (ARMD), four had myopic CNVM, 14 had diabetic retinopathy (DR), and seven had macular edema – secondary to retinal vein occlusion. Aflibercept was given in 11 (25.6%) of the study participants, of which six had DR, four had CNVM-Myopia, and one patient had macular edema – secondary to retinal vein occlusion. Conclusion: In our study, both anti-VEGF agents showed significant reduction in central macular thickness (CMT) after every injection. Our study suggests that Aflibercept is more effective in reducing CMT.